MODERN PERSPECTIVES ON DIAGNOSIS AND SURGICAL TREATMENT OF HIATAL HERNIA - Oktyabr R. Teshayev; Adkhamjon B. Babajonov (Central Asian Journal of Medicine, 2024)
This comprehensive review analyzes modern approaches to diagnosis and surgical treatment of hiatal hernia (HH) based on literature from 2013-2023. The study examines epidemiology, pathogenesis, and advances in diagnostic methods, including high-resolution manometry and functional imaging. Laparoscopic fundoplication remains the gold standard for surgical treatment, while robotic surgery and endoscopic methods offer new possibilities for treatment individualization. The implementation of enhanced recovery protocols has improved short-term outcomes. The review emphasizes the importance of personalized approaches considering anatomical features, functional parameters, and patient characteristics. Development of new materials and techniques for hiatal repair continues to be an active area of research.